20 Years of Efforts to Establish and Implement a Quality Assurance System in Greek Higher Education - Kavasakalis, Aggelos; Stamelos, George (Mediterranean Journal of Social Sciences, 2011)
The establishment and implementation of a quality assurance system in Greek universities is a policy theme that alwaysreinforced the conflict in the specific policy arena. Policy document analysis is used for the analysis of the efforts on producing andimplementing such policies. Relevant data is drawn by a larger scale research, in which, higher education is considered as a policy arenawhere actors form networks that try to translate their common beliefs into public policy. Paper’s hypothesis is that quality assurancepolicies in Greek universities are being developed following and in agreement with corresponding European education policies since Greeceis both an EU member and a participant on Bologna process. Although these external influences result the establishment of relative toEuropean developments legislative framework, Greek governments face hindrances during implementation of these policies. To overcomethe intense and reactions they indirectly prompt evaluation of universities by various, not institutionalized, evaluation programs.